PENGEMBANGAN E-MODUL PENDIDIKAN PANCASILA BERBASIS GOOGLE SITES TERINTEGRASI DENGAN BLOOKET UNTUK MENINGKATKAN KEMAMPUAN BERNALAR KRITIS SISWA KELAS IV MADRASAH IBTIDAIYAH - Arum; Muhammad Romadlon Habibullah; Firda Zakiyatur Rofi’ah (Al-Aulad: Journal of Islamic Primary Education, 2025)
Pancasila education at MI Al-Falah still relies on printed modules that are less interactive and engaging, causing the learning process to be mostly one-way. This condition makes students passive in exploring the meaning of Pancasila values and less trained in analyzing, evaluating, and drawing conclusions about moral issues around them, which are essential components of critical thinking skills. This study aims to develop a Google Sites-based e-module integrated with Blooket on the topic “Pancasila in Myself: The Meaning of Pancasila Principles in Society,” and to examine its outcomes and effectiveness in improving the critical thinking dimension of the Pancasila Student Profile Rahmatan lil Alamin (P5PPRA), which is an Indonesian character education framework emphasizing faith-based morality and civic values, among fourth grade students at MI Al-Falah. The research employed a Research and Development (R&D) method using the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The findings revealed an increase in the students’ average scores from 67 to 90, with an N-Gain of 0.70, categorized as high, indicating a significant improvement in students’ critical thinking skills. Student responses reached 92%, indicating a very positive perception. Based on these results, the e-module is considered feasible, valid, and effective in enhancing students’ critical thinking through an interactive digital approach. This e-module serves as a relevant alternative learning resource that supports the development of the critical thinking dimension of the P5PPRA character in the era of modern education.